Eye position affects flight altitude in visual approach to landing independent of level of expertise of pilot - Jacobs, David M.; Morice, Antoine H. P.; Camachon, Cyril; Montagne, Gilles (PLOS ONE, 2018)
The present study addresses the effect of the eye position in the cockpit on the flight altitude during the final approach to landing. Three groups of participants with different levels of expertise (novices, trainees, and certified pilots) were given a laptop with a flight simulator and they were asked to maintain a 3.71° glide slope while landing. Each participant performed 40 approaches to the runway. During 8 of the approaches, the point of view that the flight simulator used to compute the visual scene was slowly raised or lowered with 4 cm with respect to the cockpit, hence moving the projection of the visible part of the cockpit down or up in the visible scene in a hardly noticeable manner. The increases and decreases in the simulated eye height led to increases and decreases in the altitude of the approach trajectories, for all three groups of participants. On the basis of these results, it is argued that the eye position of pilots during visual approaches is a factor that contributes to the risk of black hole accidents.